Off-label and investigational drugs in the treatment of alcohol use disorder: A critical review - Fischler, Pascal Valentin; Soyka, Michael; Seifritz, Erich; Mutschler, Jochen (Frontiers in Pharmacology, 2022)
Compounds known to be successful in the treatment of alcohol use disorder include the aversive agent, Disulfiram, the glutamatergic NMDA receptor antagonist, Acamprosate, and the opioid receptor antagonists, Naltrexone and Nalmefene. Although all four are effective in maintaining abstinence or reduction of alcohol consumption, only a small percentage of patients receive pharmacological treatment. In addition, many other substances have been investigated for their therapeutic potential in the treatment of alcohol use disorder. In this review we summarize and compare Baclofen, Gabapentin, Topiramate, Ondansetron, Varenicline, Aripiprazole, Quetiapine, Clozapine, Antidepressants, Lithium, Neuropeptide Y, Neuropeptide S, CRF antagonists, Oxytocin, PF-05190457, Memantine, Ifenprodil, Samidorphan, Ondelopran, ABT-436, SSR149415, Mifepristone, Ibudilast, Citicoline, Rimonabant, Surinabant, AM4113 and Gamma-hydroxybutyrate (GHB). While some have shown promising results in the treatment of alcohol use disorder, others have disappointed and should be excluded from further investigation. Here we discuss the most promising results and highlight substances that deserve further study. Effective, patient-tailored treatment will require greater understanding provided by many more preclinical and clinical studies.